Dissoconiaceae associated with sooty blotch and flyspeck on fruits in China and the United States - Li, H.Y. (Nationaal Herbarium Nederland & Centraallbureau voor Schimmelcultures, 2012)
Zasmidium angulare, a novel species of Mycosphaerellaceae, and several novel taxa that reside in Dissoconiaceae, were identified from a collection of apples and Cucurbita maxima (cv. Blue Hubbard) from China and the USA that exhibited sooty blotch and flyspeck (SBFS) signs on their host substrata. Morphology on fruit surfaces and in culture, and phylogenetic analyses of the nuclear ribosomal DNAs 28S and internal transcribed spacer regions, as well as partial translation elongation factor 1-alpha gene sequences in some cases, were used to delineate seven previously unidentified species and three known species. Pseudoveronaea was established as a new genus of Dissoconiaceae, represented by two species, P. ellipsoidea and P. obclavata. Although Pseudoveronaea was morphologically similar to Veronaea, these fungi clustered with Dissoconiaceae (Capnodiales) rather than Chaetothyriales (Herpotrichiellaceae). Ramichloridium mali comb. nov., and three novel species, R. cucurbitae, R. luteum and R. punctatum were closely related with R. apiculatum, which together formed a distinct subclade in Dissoconiaceae. Species of Dissoconium s.lat. clustered in two well-supported clades supported by distinct morphological and cultural features. Subsequently Uwebraunia, a former synonym of Dissoconium, was resurrected for the one clade, with new combinations proposed for U. australiensis, U. commune, U. dekkeri and U. musae. Furthermore, we also reported that D. aciculare, Dissoconium sp., U. commune and U. dekkeri were associated with SBFS on apples.